International norm development: cyclic model of norm change and self-determination - Kang, Sang June (2018)
With the surge of constructivism, which values non-material factors and ideational variables, norm research became the center of interest in International Relations scholarship. The early constructivist theory is suitable for showing how a norm could be replaced by another but incapable of explaining how a norm itself changes. Hence, the next challenge for constructivism would be demonstrating a norm change mechanism. The purpose of this research is to fill a gap in the international norm literature. From a constructivist perspective, this research suggests a cyclic model of international norm change and verifies its plausibility by examining the empirical evidence of change in the international norm of self-determination. Although self-determination is one of the essential norms in the contemporary international order, it has yet to be investigated within international norm literature. Unlike the static model of early constructivists, the cyclic model of international norm change demonstrates a clear framework to see how the norm of self-determination has changed over time and explains why norm structures are sometimes stable and other times volatile.